Corneal Viscoelastic Properties in Patients with Angioid Streaks. (3rd March 2016) - Yildirim, Rengin; Dikkaya, Funda; Arici, Ceyhun; Comlekoglu, Didar Ucar
Abstract: Purpose : The aim of this study is to investigate the possible corneal biomechanical changes in patients with angioid streaks and to understand if the calcified and thickened Bruch's membrane associated with angioid streaks influences elasticity of the eye and intraocular pressure. Materials and Methods : Twelve eyes of 12 patients with angioid streaks (six males and six females) and 12 eyes of 12 age- and sex-matched healthy volunteers were enrolled in the study. Corneal hysteresis (CH), corneal resistance factor (CRF), corneal compensated intraocular pressure (IOPcc) and Goldmann-correlated intraocular pressure (IOPg) were measured with an Ocular Response Analyzer (ORA). Central corneal thickness (CCT) was measured with an ultrasound pachymeter. Results : Mean CRF and IOPg values in eyes with angioid streaks (12.10 ± 1.27 and 17.76 ± 2.73, respectively) were significantly higher than those in matched control eyes (10.70 ± 1.28 and 14.67 ± 2.72, respectively; p  = 0.01 for CRF, p  = 0.007 for IOPg). There was no statistically significant difference between eyes with angioid streaks and matched control eyes in measured CH, IOPcc and CCT values ( p  = 0.29, p  = 0.09 and p  = 0.86, respectively). Conclusions : This study revealed that angioid streaks can affect corneal biomechanical properties by increasing CRF, as compared to the healthy eyes. Increased CRF means increased resistance for effect of IOP on eye so it can be speculated that these patients tend to be more protected for glaucoma.